A computational study of suppression of sharp wave ripple complexes by controlling calcium and gap junctions in pyramidal cells. Issue 1 (1st January 2021) - Mushtaq, Muhammad; Haq, Rizwan ul; Anwar, Waqas; Marshall, Lisa; Bazhenov, Maxim; Zia, Kashif; Alam, Hina; Hertel, Lars; Awan, Abdul Aleem; Martinetz, Thomas
ABSTRACT: The hippocampus plays a key role in memory formation and learning. According to the concept of active systems memory consolidation, transiently stored memory traces are transferred from the hippocampus into the neocortex for permanent storage. This phenomenon relies on hippocampal network oscillations, particularly sharp wave ripples [SPW-Rs). In this process prior saved data in the hippocampus may be reactivated. Recent investigations reveal that several neurotransmitters and neuromodulators including norepinephrine, acetylcholine, serotonin, etc., suppress SPW-Rs activity in rodents' hippocampal slices. This suppression of SPW-Rs may depend on various presynaptic and postsynaptic parameters including decrease in calcium influx, hyperpolarization/depolarization and alteration in gap junctions' function in pyramidal cells. In this study, we demonstrate the impact of calcium influx and gap junctions on pyramidal cells for the modulation of SPW-Rs in a computational model of CA1. We used, SPW-Rs model with some modifications. SPW-Rs are simulated with gradual reduction of calcium and with decreasing conductance through gap junctions in PCs. Both, with calcium reduction as well as with conductance reduction through gap junctions, SPW-Rs are suppressed. Both effects add up synergistically in combination. Graphical abstract: uf0001